2018
DOI: 10.1096/fj.201700915r
|View full text |Cite
|
Sign up to set email alerts
|

Severe negative energy balance during 21 d at high altitude decreases fat‐free mass regardless of dietary protein intake: a randomized controlled trial

Abstract: In this 2-phase randomized controlled study, we examined whether consuming a higher-protein (HP) diet would attenuate fat-free mass (FFM) loss during energy deficit (ED) at high altitude (HA) in 17 healthy males (mean 6 SD: 23 6 6 yr; 82 6 14 kg). During phase 1 at sea level (SL, 55 m), participants consumed a eucaloric diet providing standard protein (SP; 1.0 g protein/kg,) for 21 d. During phase 2, participants resided at HA (4300 m) for 22 d and were randomly assigned to either an SP or HP (2.0 g protein/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(112 citation statements)
references
References 61 publications
8
104
0
Order By: Relevance
“…This lack of an effect may also be related to the study design, as HIGH and LOW were on equally energy‐restricted diets throughout the 10‐day exercise, exposing soldiers in the two groups to similar energy‐dependent catabolic signaling. This perspective is supported by a recent study, wherein an intervention with similar dietary groups (1 g kg −1 d −1 protein vs 2 g kg −1 d −1 protein, isocaloric) and similar levels of energy deficiency (−70%) disclosed no effect of additional protein intake on FFM. The authors thus concluded that increased protein intake during prolonged periods of negative energy balance seems to be used for energy metabolic purposes, which is also supported from findings in another protein supplementation study using isocaloric energy‐restricted diet .…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…This lack of an effect may also be related to the study design, as HIGH and LOW were on equally energy‐restricted diets throughout the 10‐day exercise, exposing soldiers in the two groups to similar energy‐dependent catabolic signaling. This perspective is supported by a recent study, wherein an intervention with similar dietary groups (1 g kg −1 d −1 protein vs 2 g kg −1 d −1 protein, isocaloric) and similar levels of energy deficiency (−70%) disclosed no effect of additional protein intake on FFM. The authors thus concluded that increased protein intake during prolonged periods of negative energy balance seems to be used for energy metabolic purposes, which is also supported from findings in another protein supplementation study using isocaloric energy‐restricted diet .…”
Section: Discussionsupporting
confidence: 74%
“…This perspective is supported by a recent study, wherein an intervention with similar dietary groups (1 g kg −1 d −1 protein vs 2 g kg −1 d −1 protein, isocaloric) and similar levels of energy deficiency (−70%) disclosed no effect of additional protein intake on FFM. The authors thus concluded that increased protein intake during prolonged periods of negative energy balance seems to be used for energy metabolic purposes, which is also supported from findings in another protein supplementation study using isocaloric energy‐restricted diet . Indeed, most studies that reveal beneficial effects of increased protein ingestion on FFM during prolonged periods of energy restriction intake, involve intake of surplus protein as an additive to the regular diet, with a concomitant increase in overall energy intake.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations